'But that wasn't enough': exploring affective assemblages within a professional relationship. Issue 4 (4th July 2017) - Henderson, Linda
ABSTRACT: This paper engages with the early childhood–school relationship. The relationship has a long-standing history of being defined by a series of divisions and separations. Research has identified the divisions and separations to be largely determined by differences around concepts of learning and pedagogy. Discursive analyses of these differences often result in a series of impasses. The aim of this paper is to move beyond these discursively determined impasses. I draw on data from a small pilot study where a group of early childhood teachers come together to talk about their use of Transition Statements. I bring to the analysis of the data the concept of affective assemblages. This allows me to look beyond that which has been discursively produced in order to ask new questions, and to offer new ways of being in relationship.